Efficacy of Various Biopesticides against Red Ant (Dorylus orientalis Westwood) in Potato Field - Sabin Bhattarai; Bikram Nepali; Manoj Bhatta; Ananta Raj Devkota; Jiban Shrestha (Hasanuddin University, 2022)
Red ant (Dorylus orientalis Westwood) is the most destructive insect pest of potato tubers in the field in Nepal. A field experiment was conducted at Bhatkada, Dadeldhura district, Nepal in 2020 to determine the efficacy of various biopesticides and chemical insecticide on red ants. The plot size in this experiment was 106.7 m2. Five treatments viz. Chlorpyriphos 20% EC (2 mL L-1 water), Banmaara (2 kg plot-1), Cow urine (2 L 6 L-1water plot-1), Agave (25 g tuber-1) and Control (no treatment) were evaluated in randomized complete block design with four replications. The data on plant height and the number of leaves were taken at 45, 60, and 75 days after planting (DAP). The data on slightly and severely infested tubers were taken after harvesting of potato. The results showed that Chlorpyriphos treated plots gave the lowest values of traits viz numbers of slightly infested tuber (91,500 ha-1), severely infested tubers (12,500 ha-1), weights of slight infested tubers (7,700 kg ha-1) and severely infested tuber (1,130 kg ha-1). Among the botanical pesticides, Agave treated plots provided the second lowest values of numbers of slightly infested tuber (145,500 ha-1), severely infested tubers (37,400 ha-1), weights of slight infested tubers (13,400 kg ha-1) and severely infested tuber (3,110 kg ha-1). The results showed that the Agave treatment provided the highest marketable yield (50,900 kg ha-1). Thus, Chlorpyriphos and Agave could be used to efficiently protect potato tubers from red ant in potato field.